1998
DOI: 10.1037/0022-3514.74.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Everyday lies in close and casual relationships.

Abstract: n 2 diary studies, 77 undergraduates and 70 community members recorded their social interactions and lies for a week. Because lying violates the openness and authenticity that people value in their close relationships, we predicted (and found) that participants would tell fewer lies per social interaction to the people to whom they felt closer and would feel more uncomfortable when they did lie to those people. Because altruistic lies can communicate caring, we also predicted (and found) that relatively more o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
400
1
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(425 citation statements)
references
References 39 publications
(93 reference statements)
16
400
1
8
Order By: Relevance
“…The relationship between compassion and prosocial lying may differ depending on the in-group/out-group membership of the lie target, or the lie teller's perceived closeness to the target. People feel more compassion towards those to whom they are closely related (Cialdini et al, 1997), and people also tell more prosocial lies to close others than selfish lies (DePaulo & Kashy, 1998). Thus, it is possible that an interaction exists between compassion and the closeness of the lie target on prosocial lying, such that compassion would exert an even stronger influence on prosocial lies told between friends, coworkers, or relationship partners.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between compassion and prosocial lying may differ depending on the in-group/out-group membership of the lie target, or the lie teller's perceived closeness to the target. People feel more compassion towards those to whom they are closely related (Cialdini et al, 1997), and people also tell more prosocial lies to close others than selfish lies (DePaulo & Kashy, 1998). Thus, it is possible that an interaction exists between compassion and the closeness of the lie target on prosocial lying, such that compassion would exert an even stronger influence on prosocial lies told between friends, coworkers, or relationship partners.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DePaulo and Kashy (1998) found that lying was commonplace, but that people were selective with respect to the types of lies they were willing to tell and to whom they were willing to tell them. The theory of self-concept maintenance (Mazar et al, 2008) models this approach to engaging in unethical behavior.…”
Section: Hypothesis 1 Mindfulness Is Associated With a Lower Incidenmentioning
confidence: 99%
“…One exception is the situation in which truthful information may harm another individual's feeling. In this situation, lying is sometimes condoned or practiced (Bussey, 1999;DePaulo & Bell, 1996;DePaulo & Kashy, 1998;Lee & Ross, 1997;Sweetser, 1987).In Chinese society, the Western egalitarian notion of the free flow of information does not hold. The principle of veracity is based neither solely on information accuracy nor on whether truthful information may harm another individual's feeling.…”
mentioning
confidence: 99%